The Influence of Emotional Intelligence on Work-life Balance - Indraswari, Dara Kania (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Over the past few decades, work-life balance has become a major issue that occurs in work, not only in one type of work, but in all types of work. Work-life balance is a major issue in work, this cannot be separated from the high work demands and excessive working hours which have now become the norm (Kumarasamy, Pangil, & Mohd Isa, 2016). It is important for individuals who work to have Emotional intelligence, making individuals have the ability to separate the life they are living so as to avoid conflicts between personal life and work life. The aim of this research is to determine the relationship between Emotional intelligence and Work-life balance. This research uses a literature review method, namely by collecting library information and data. It was found that work-life balance is greatly influenced by emotional intelligence.